Resposta de cultivares de feijão à inoculação com rizóbio e co-inoculação de rizóbio + azospirillum, aplicados via semente e solo - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The common bean plant holds significant social and economic importance in various countries, serving as a vital protein source. Its cultivation requires a substantial demand for nitrogen, which can be supplied through the addition of one or a group of diazotrophic bacteria capable of biological nitrogen fixation. However, there is a need to gather more information regarding the responsiveness of current high-yielding genetic materials available in the market. This should be coupled with more efficient application technology, enabling this technique to be adopted on a large scale by bean farmers. Thus, the objective of this study was to evaluate nodulation, growth, and production of high-yielding common bean cultivars, subjected to rhizobial inoculation and co-inoculation of rhizobia with Azospirillum. These inoculants were applied through seed coating and soil application under field conditions. The experiments were conducted over two cropping seasons, the "wet season" of 2021/2022 in Ipameri-GO and the winter of 2022 in Anápolis-GO. A randomized block design was employed in a 4 x 2 x 2 + 8 factorial arrangement with three replications. Treatments consisted of four common bean cultivars (BRS FC 402, BRS Estilo, BRS Pitanga, and BRS Esteio) subjected to rhizobial inoculation, co-inoculation of rhizobia + Azospirillum, applied either via seed coating or soil application, along with eight additional treatments corresponding to mineral nitrogen source fertilization and its absence (control) for each cultivar studied. Nodulation, plant morphophysiology, yield components, grain yield, and final plant stand were assessed. The study results show that the co inoculation with R. tropici + A. brasilense technique, applied through soil, enhances the morphological and agronomic aspects of common bean plants. The BRS Estilo and BRS Esteio cultivars, with yields of 2049.3 and 1830.7 kg ha-1, respectively, demonstrated better grain yields when coinoculated through the soil. Co-inoculation with R. tropici + A. brasilense applied directly to the soil can be used as an alternative to nitrogen fertilization.
Response of bean cultivars to inoculation with rhizobium and co-inoculation of rhizobium + azospirillum, applied via seed and soil
Keywords: P. vulgaris; Nutrição; FBN; Nodulação; Produtividade; Nutrition; Biological nitrogen fixation; Nodulation; Yield; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS